2020
DOI: 10.21203/rs.3.rs-33595/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered expression profile of BAFF receptors on peripheral blood B lymphocytes in Graves’ Disease

Abstract: Background: B lymphocyte activating factor (BAFF) is a growth factor regulating B lymphocytes survival and maturation. Serum BAFF levels were elevated in patients affected with autoimmune thyroid diseases (AITD), including Graves’ disease (GD) and Hashimoto’s thyroiditis (HT). The aim of this study is to investigate the association of expression of BAFF receptors on the peripheral blood B lymphocytes in addition to serum BAFF concentrations in patients affected with GD.Methods: Fifty-two GD patients, 39 Hashim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Similarly, the association of rs9514828 and rs4000607 in UK patients with GD have been reported that can change the gene expression (Lane et al 2019). As an underlying molecular mechanism, Wang et al showed that the skewed expression profile of BAFF receptors on B lymphocytes may mediate autoimmunity in GD, suggesting that restoring the normal expression profile can be a new strategy for GD treatment (Wang et al 2020). In other words, blocking the interaction of BAFF with its receptor negatively affects B-cell proliferation, indirectly decreasing B-cell survival and reducing the production of autoantibodies in GD (Lane et al 2020).…”
Section: Other Important Genes In the Immune Systemmentioning
confidence: 96%
“…Similarly, the association of rs9514828 and rs4000607 in UK patients with GD have been reported that can change the gene expression (Lane et al 2019). As an underlying molecular mechanism, Wang et al showed that the skewed expression profile of BAFF receptors on B lymphocytes may mediate autoimmunity in GD, suggesting that restoring the normal expression profile can be a new strategy for GD treatment (Wang et al 2020). In other words, blocking the interaction of BAFF with its receptor negatively affects B-cell proliferation, indirectly decreasing B-cell survival and reducing the production of autoantibodies in GD (Lane et al 2020).…”
Section: Other Important Genes In the Immune Systemmentioning
confidence: 96%